Uma pedagogia das possibilidades: gestão colaborativa, práticas educativas e organização curricular - Perin, Angelita Tatiane Silva dos Santos (2017)
The main objective of this research was to understand the limits and possibilities regarding collaborative management at the Joceli Corrêa High School, located in the city of Jóia, RS, with a view to qualifying pedagogic practices in High School. This is a qualitative research, whose technical procedure was the interpretive research using the following data construction and analysis procedures: participant observation, dialog groups, questionnaires, document analysis and content analysis. The research collaborators were educators, high school graduates and high school students, as well as the E.E.E.M. Joceli Corrêa. In relation to High School, the research found its contribution in Corso and Soares (2014), Silva (2017), among others, besides legal documents. For the collaborative management, a foundation was found in Lück (2006, 2007, 2011), while research as a scientific and educational principle was endorsed in Demo (2011) and Minayo (2010). Rural education was subsidized in Caldart (1997, 2000, 2009, 2012) and Janata (2014). The research actions prioritized the recognition of how the school management processes are being constituted in this school, in the historical social perspective, with a look at the educational work developed in High School, considering the school and pedagogical management within its limits and possibilities. Also, we sought to unveil and understand the dynamization and contribution of research as a pedagogical and educational principle along with the Proposal for Secondary Education. Finally, it was prioritized to contribute with the elaboration of a strategic plan focused on the qualification of the pedagogical management processes in High School. It is concluded that the collaborative management has been present in School since its genesis and that with the Secondary School it has improved, having passed through qualifying moments during Polytechnic Secondary School, the bias of polytechnic and the bias of social research, because the whole movement for the research process to be improved involved the various educators in the areas of knowledge. Thus, one of the possibilities that collaborative management has enabled and can further strengthen is active participation, development of processes of observation, analysis, criticism, classification, choice of ways, exercising power over the educational process and how to learn. In this context, the processes that are developed generate the committed responsibility of the subjects that act jointly in the accomplishment of the purposes. was verified that it is important to dynamize the precepts and priorities of the School's Political-Pedagogical Project, considering a strategic planning process for curricular development, representing the possibility to change the context, the school practices and the conceptions of the subjects that perform. Thus, the strategic plan, the product of this professional master's research, is based on planning the limits and possibilities pointed out by the collaborating subjects and constitutes a democratic and collaborative tool to convert intentions into achievements, with a view to consolidating good practices, strengthening human relations and educational work, as well as producing shared knowledge and historical partner with the entire school community.